2021
DOI: 10.1038/s41598-021-93053-7
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of circulating hybrid cells as a non-invasive biomarker for myriad solid tumors

Abstract: Metastatic progression defines the final stages of tumor evolution and underlies the majority of cancer-related deaths. The heterogeneity in disseminated tumor cell populations capable of seeding and growing in distant organ sites contributes to the development of treatment resistant disease. We recently reported the identification of a novel tumor-derived cell population, circulating hybrid cells (CHCs), harboring attributes from both macrophages and neoplastic cells, including functional characteristics impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 68 publications
3
61
0
2
Order By: Relevance
“…Only one population of aneuploid CD45 ─ CECs demonstrated the most transcriptional cancer features that may indicate the presence of an aggressive subset of CTCs. Interestingly, no important molecular features were identified in aneuploid CD45 + CECs; however, tumor hybrid cells are known to have increased proliferation and migration, drug resistance, decreased apoptosis rate, and avoiding immune surveillance [14][15][16] . Diploid CD45 ─ and CD45 + CECs included different normal cells (stem, bone marrowderived mononuclear, B, T, and NK cells) and were enriched by Th1 and Th2 cell differentiation, oxidative phosphorylation hematopoietic cell lineage, necroptosis, and other signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Only one population of aneuploid CD45 ─ CECs demonstrated the most transcriptional cancer features that may indicate the presence of an aggressive subset of CTCs. Interestingly, no important molecular features were identified in aneuploid CD45 + CECs; however, tumor hybrid cells are known to have increased proliferation and migration, drug resistance, decreased apoptosis rate, and avoiding immune surveillance [14][15][16] . Diploid CD45 ─ and CD45 + CECs included different normal cells (stem, bone marrowderived mononuclear, B, T, and NK cells) and were enriched by Th1 and Th2 cell differentiation, oxidative phosphorylation hematopoietic cell lineage, necroptosis, and other signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a comparison of hybrid clone cells formed by spontaneous fusion events of human M13SV1-EGFP-Neo breast epithelial cells and HS578T-Hyg, MDA-MB-435-Hyg, and MDA-MB-231-Hyg cancer cells demonstrated that fusion cells formed by HS578 cells had stronger in vitro tumor-initiating traits as compared to those formed by MDA-MB-231 and MDA-MB-453 cells, as identified by surface marker (frequency of ALDH1+ cells) and functional (mammosphere) assays ( Fahlbusch et al, 2020 ). Similarly, hybrid cells in circulation were shown to reflect the heterogeneity of both epithelial and non-epithelial malignancies and can be used as a translational non-invasive readout of tumor aggressiveness, given their higher frequency than that of CTCs ( Dietz et al, 2021 ). Hybrid clones can also be metabolically heterogeneous, as noted for subpopulations of CSCs with varying EMT phenotypes ( Luo et al, 2018 ), but overall, they display an enriched Warburg-like phenotype (upregulated glycolysis) ( Brito et al, 2021 ).…”
Section: Role Of Tumor Hybrid Cells In Drug Resistancementioning
confidence: 99%
“…These cells were called “circulating hybrid cells” or CHCs. They were also detected in the blood of oncological patients in numbers far larger than the quantities of CTCs – on average approximately 5-70 cells per 500,000 live cells depending on the type of oncological disease, up to thousands in the cases of uveal melanoma [ 61 ]. It was hypothesized that CHCs are the products of cell fusion, when CAMLs are produced as a result of engulfing of cancer cells [ 57 ].…”
Section: Characteristic Of Hybrid Cancer Cellsmentioning
confidence: 99%